Nurses dealing with ethical conflicts in time of pandemic - Rivero Mamani, Angela Kristell (2021)
The COVID19 disease, caused by the new coronavirus, SARS-Cov2, has caused health personnel to face once again a major pandemic, and use the best of their knowledge and skills to help the sick. Health professionals, doctors, nurses, nursing technicians, laboratory workers, biologists, and others faced this disease with all their knowledge, despite the difficulties, with the sole goal of achieving the recovery of their patients. Nurses fulfill the role of caregivers with their patients, this is one of the great objectives of their profession. The nursing care provided in this pandemic was altered due to various challenges that nurses had to go through due to the lack of medical supplies, death of their patients, family involvement, work overload, fear of contagion, among others; generating in them problems in their mental health, moral anguish, and negative feelings such as anguish, frustration, impotence.  Despite all these events, nurses continued trying to provide quality care to their patients despite limitations and facing these bioethical challenges.